Multifunctional Polymer‐Coated Carbon Nanotubes for Safe Drug Delivery. (28th February 2013) - Moore, Thomas L.; Pitzer, Joshua E.; Podila, Ramakrishna; Wang, Xiaojia; Lewis, Robert L.; Grimes, Stuart W.; Wilson, James R.; Skjervold, Even; Brown, Jared M.; Rao, Apparao; Alexis, Frank
<x xml:space="preserve">Abstract</x> Although progress in the use carbon nanotubes in medicine has been most encouraging for therapeutic and diagnostic applications, any translational success must involve overcoming the toxicological and surface functionalization challenges inherent in the use of such nanotubes. Ideally, a carbon‐nanotube‐based drug delivery system would exhibit low toxicity, sustained drug release, and persist in circulation without aggregation. Here, carbon nanotubes (CNTs) coated with a biocompatible block‐co‐polymer composed of poly(lactide)‐poly(ethylene glycol) (PLA‐PEG) are reported to reduce short‐term and long‐term toxicity, sustain drug release of paclitaxel (PTX), and prevent aggregation. The copolymer coating on the surface of CNTs significantly reduces in vitro toxicity. Moreover, the coating reduces the in vitro inflammatory response. Compared to non‐coated CNTs, in vivo studies show no long‐term inflammatory response with CNT coated with PLA‐PEG (CLP) and the surface coating significantly decreases acute toxicity by doubling the maximum tolerated dose in mice. In vivo biodistribution and histology studies suggest a lower degree of aggregation in tissues.